The effect of sodium on cardio-respiratory health - Pogson, Zara (2009)
Background This thesis investigates the effect of sodium modification on asthma and heart rate variability (HRV) using a randomised controlled study design. Cross-sectional data were used to assess novel markers of asthma control and if serum osmolality was inversely associated with lung function.